Organic input incorporation for enhancing sustainability and economic viability of cowpea in North-Western Himalayan region - Sharma, Tarun; Singh, Janardan; Madaik, Sparsh; Kumar, Pardeep; Singh, Akashdeep; Rana, Bharat Bhushan; Chauhan, Garima (Frontiers in Agronomy, 2024)
Cowpea (Vigna unguiculata L. [Walp.]) cultivation encounters a plethora of challenges such as suboptimal productivity levels, declined income levels, and poor soil health under conventional fertilization systems. Therefore, the present field investigation was undertaken at the Research Farm, Department of Agronomy, CSKHPKV, Palampur in the rainy season of 2019 to evaluate eight combinations of organic farming and Zero Budget Natural Farming (NF) based inputs, i.e., Beejamrita (100 ml kg−1 of seed) + Jeewamrita (187.5 L ha−1); Beejamrita (100 ml kg−1 of seed) + GhanaJeewamrita (250 kg ha−1); Beejamrita (100 ml kg−1 of seed) + Jeewamrita (187.5 L ha−1) + GhanaJeewamrita (250 kg ha−1); farm yard manure (FYM) 10 Mg ha−1; FYM (10 Mg ha−1) + GhanaJeewamrita (250 kg ha−1); biofertilizers (PSBs and Rhizobium at 10 g kg−1 of seed) + FYM (10 Mg ha−1) + vermiwash (1:10); biofertilizers (PSBs and Rhizobium at 10 g kg−1 of seed) + vermicompost (7.5 Mg ha−1) + vermiwash (1:10); absolute (untreated) control; in a randomized complete block design with three replications for their influence over cowpea productivity, profitability, and energetics. The results of the investigation revealed that applying FYM (10 Mg ha−1) and GhanaJeewamrita (250 kg ha−1) in combination resulted in significantly higher grain yield(1,070.5 kg ha−1), economic net returns (766.61 USD ha−1), net energy gains (78,230 MJ ha−1), and considerably improved soil microbial biomass carbon (133.92 mg g−1 of soil), nitrogen (27.40 mg g−1 of soil), urease (52.20 (mg g−1 urea of soil h−1), and dehydrogenase activity (5.21mg g−1 TPF of soil h−1). Improved soil biological properties in the present study might have been responsible for considerable increment in cowpea yield and profitability. Therefore, in-combination application-based module of FYM (10 Mg ha−1) and GhanaJeewamrita (250 kg ha−1) can be recommended for enhancing productivity and profitability of cowpea cultivation under North-Western Himalayan agro-ecological conditions. This study contributes valuable insights for organic input strategies in regions facing similar challenges.